2015
DOI: 10.1103/physreve.92.010902
|View full text |Cite
|
Sign up to set email alerts
|

Predicting chaotic time series with a partial model

Abstract: Methods for forecasting time series are a critical aspect of the understanding and control of complex networks. When the model of the network is unknown, nonparametric methods for prediction have been developed, based on concepts of attractor reconstruction pioneered by Takens and others. In this Rapid Communication we consider how to make use of a subset of the system equations, if they are known, to improve the predictive capability of forecasting methods. A counterintuitive implication of the results is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…When a priori knowledge on the physical system is available, one of the standard approaches to reconstruct the nonlinear dynamics from an incomplete data set is to design a statistical model that incorporates the physical knowledge [15,16,17]. In [18], it is shown that a high-resolution temporal dynamics can be reconstructed from a low-resolution time series data, which has a 10 times lower time resolution, by using only a subset of the governing equations. Incorporating the physics knowledge on the training of ANN, [6] proposed "physics informed neural network", which can recover the complex nonlinear dynamics from only a small fraction of the data.It is challenging to reconstruct nonlinear dynamics without having any prior knowledge on the underlying process.…”
mentioning
confidence: 99%
“…When a priori knowledge on the physical system is available, one of the standard approaches to reconstruct the nonlinear dynamics from an incomplete data set is to design a statistical model that incorporates the physical knowledge [15,16,17]. In [18], it is shown that a high-resolution temporal dynamics can be reconstructed from a low-resolution time series data, which has a 10 times lower time resolution, by using only a subset of the governing equations. Incorporating the physics knowledge on the training of ANN, [6] proposed "physics informed neural network", which can recover the complex nonlinear dynamics from only a small fraction of the data.It is challenging to reconstruct nonlinear dynamics without having any prior knowledge on the underlying process.…”
mentioning
confidence: 99%
“…Nowadays, the Lorenz system is a popular test model for new methods in such fields as machine learning and forecasting (e.g. [13,30,18]).…”
Section: A Brief Overview Of Lorenz'63mentioning
confidence: 99%
“…For the nonlinear filtering with known transition functions, particle filters, or sequential Monte Carlo methods, provide a very powerful tool for the modeling of non-Gaussian distributions [13,14]. While most of these nonlinear filtering models require at least a partial knowledge of the dynamical system [15], in many problems, we do not have knowledge about the underlying physical processes, or the system is too complex to develop a model from the first principles [16].…”
Section: Introductionmentioning
confidence: 99%